CORPORATE GOVERNANCE DALAM KEPUTUSAN HEDGING PADA MASA SEBELUM DAN SELAMA PANDEMI COVID-19 - Tjandra, Andy Yesaya; Irwanto, Andry (Buletin Studi Ekonomi; VOL.27.NO.1.FEBRUARI 2022, 2022)
This study was conducted to determine the effect of corporate governance mechanisms with profitability and leverage as variable control on hedging decisions in manufacturing companies listed on the Indonesia Stock Exchange for period 2019-2020. This research was conducted using a quantitative approach with logistic regression research methods. The sample in this study amounted to 183 companies. The results of this study indicate that board of commissioners has positive and significant, independent commissioner has positive and not significant, institutional ownership has negative and not significant, managerial ownership has negative and not significant, family duality has negative and not significant influence before and during the pandemic Covid-19 and there are no differences in corporate governance mechanisms that have the most significant influence on hedging decisions before and during pandemic Covid-19.